Islands of sovereignty : Haitian migration and the borders of empire - Kahn, Jeffrey S. (Chicago : The University of Chicago Press, 2019)
In 'Islands of Sovereignty', anthropologist and legal scholar Jeffrey S. Kahn offers a new interpretation of the transformation of US borders during the late twentieth century and its implications for our understanding of the nation-state as a legal and political form.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 22, 2019).
Keywords: United States -- Emigration and immigration -- Government policy; United States -- Emigration and immigration; Emigration and immigration law -- United States; Coastal surveillance -- United States; Refugees -- Legal status, laws, etc. -- United States; Refugees -- Haiti; Haiti -- Emigration and immigration; Border security -- United States; Politics and Government; Politics & government